2012
DOI: 10.4028/www.scientific.net/amr.626.131
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterization of Fe<sub>3</sub>O<sub>4</sub>/TiO<sub>2</sub> Composites by Heteroagglomeration

Abstract: Fe3O4/TiO2composites were prepared by heteroagglomeration. The composites of different Fe3O4to TiO2weight ratio were prepared by mixing of prepared Fe3O4with TiO2in aqueous slurry, under ultrasonic treatment. All prepared samples were characterized by XRD, VSM, SEM/EDS, raman spectroscopy and BET. The prepared composites contained TiO2(anatase and rutile) and Fe3O4crystal phases. The magnetization hysteresis loop for Fe3O4/TiO2nanocomposites indicated that the hybrid catalyst showed superparamagnetic character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Heteroagglomeration may result in permanent contact via interactions between the electrostatic forces of two particles that differ in charge (Islam et al, 1995;Fisli et al, 2013). The isoelectric point (IEP) of TiO 2 is approximately 6.2 (Suttiponparnit et al, 2011), while the isoelectric point of Fe 3 O 4 /SiO 2 is about 3 (Fisli et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Heteroagglomeration may result in permanent contact via interactions between the electrostatic forces of two particles that differ in charge (Islam et al, 1995;Fisli et al, 2013). The isoelectric point (IEP) of TiO 2 is approximately 6.2 (Suttiponparnit et al, 2011), while the isoelectric point of Fe 3 O 4 /SiO 2 is about 3 (Fisli et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, some nanoferrites like ZnFe 2 O 4 have shown desirable degradation efficiency of organic target compounds under both visible light and UV irradiation [164]. Similar studies have reported degradation of different contaminants using Fe 3 O 4 [165][166][167] (Table 3). A schematic of the use of magnetic nanophotocatalysts (MNPCs) in water treatment [173] is illustrated in Figure 8.…”
Section: Magnetic Nanophotocatalystsmentioning
confidence: 58%
“…In the Raman spectra, it was also observed the new peaks at 226, 245 and 292 cm -1 for 30Fe/Ti and 40Fe/Ti which were ascribed to the hematite phase of iron oxide, but magnetite phase was not detected. The magnetite phase can change into hematite phase due to a temperature increase of several hundred degrees during the use of a strongly focused laser on Raman measurement [25]. Typical TEM images of 40% Fe/Ti are presented in Fig.…”
Section: Resultsmentioning
confidence: 99%